Correlation between the shoot‐cutting behavior of the acorn weevil and the reproductive traits of host fagaceous trees. Issue 4 (1st August 2019) - Hirayama, Daisuke; Okada, Minetaka; Nanami, Satoshi; Itoh, Akira
Abstract: Many fagaceous species mature acorns during the second autumn after flowering and are called "2‐year species." In 2‐year species of subgenus Cyclobalanopsis (genus Quercus ), alternate bearing (2‐year seed production cycle) is prominent, but this has not been reported for other 2‐year species in the genera of Lithocarpus and Castanopsis . We tested the hypothesis that the difference in reproduction of 2‐year species is linked to the weevil, Mechoris ursulus . After ovipositing on acorns, this insect cuts the shoots to which the acorns are attached. We examined the host preference of M. ursulus and reproductive traits of fagaceous 2‐year species. Percentage infestation was remarkably high in the subgenus Cyclobalanopsis, whereas Lithocarpus and Castanopsis species suffered almost no damage. Furthermore, unlike Lithocarpus and Castanopsis, most of the acorn‐producing shoots in subgenus Cyclobalanopsis had no current‐year shoots. The clear relationship suggests that alternate bearing in subgenus Cyclobalanopsis is an adaptation to the shoot‐cutting behavior of M. ursulus . Abstract : A clear relationship between shoot‐cutting by the acorn weevil Mechoris ursulus and the reproductive traits of host fagaceous species was found. The result supports our hypothesis that alternate‐bearing in the subgenus Cyclobalanopsis is an adaptation to the shoot‐cutting behavior of M. ursulus .